Ethnic Disparities in Risk Factors for Myopia among Han and Minority Schoolchildren in Shawan, Xinjiang, China. Issue 1 (19th January 2023) - Shi, Yumeng; Ma, Dongmei; Li, Xuemei; He, Xiaolan; Cui, Hanwen; Li, Guoqing; Wang, Jingjing; Luo, Jianfeng; Yang, Jin
Abstract : SIGNIFICANCE: The ethnic differences in myopia rates, ocular dimensions, and risk factors between Han and non-Han schoolchildren observed in this study may help fill the knowledge gap about ethnic minorities and are important for China and other countries to address vision-related health inequalities among different ethnic groups. PURPOSE: This study aimed to investigate the risk factors of juvenile myopia and elucidate the disparities of risk factors among Han and non-Han school students in Xinjiang, China. METHODS: A population-based cross-sectional study of 876 schoolchildren from grades 1 to 9 was conducted in the Anjihai Middle School in Shawan, Xinjiang Uygur Autonomous Region, China. Visual acuity and ocular biometry were assessed, and personal information, including behavior, birth status, and familial factors, was collected using self-made standardized questionnaires. RESULTS: The myopia rate among students of Han ethnicity (50.5%) was the highest, followed by Hui (41.3%) and Uygur et al. (32.0%, P < .001). Similar patterns were observed for mean axial length. The mean axial lengths are 23.7, 23.4, and 23.3 mm, respectively ( P = .01). Overall, performing high-quality eye exercises, longer sleep duration, being born in summer, parental smoking, and consuming more food containing anthocyanins were all associated with a lower incidence of myopia. Meanwhile, Han ethnicity, intensive near task, bad eye habits, and myopic mothers were associated with higher odds of myopia. After adjusting for environmental influences pertaining to myopia, the variation in myopia prevalence between Han and Uygur et al. remained significant, whereas it changed to not significant between Han and Hui ethnicities. CONCLUSIONS: Significant disparities were found in the prevalence of myopia among various ethnic groups in Shawan, Xinjiang. Life habits, birth status, and familial factors may contribute to such variance and play different roles in the occurrence of juvenile myopia among various ethnicities.